Spexin mRNA profile and its response to different photoperiods in Chinese Yangzhou geese (Anas cygnoides) - Liu, Jie; Dai, Shudi; Shao, Xibing; Wei, Chuankun; Dai, Zichun; Yang, Pengxia; Lei, Mingming; Chen, Rong; Zhu, Huanxi (Frontiers in Veterinary Science, 2022)
Spexin (SPX, NPQ), a novel neuropeptide composed of 14 amino acid residues, is evolutionarily conserved among different species. Spexin has been suggested to have pleiotropic functions in mammals. However, reports on spexin in birds are limited. To clarify the role of spexin in goose reproduction, the spexin gene was cloned and analyzed. Analysis of tissue distribution by RT-PCR showed that the expression of spexin and its two receptors was widespread. During the long photoperiod, the expression levels of spexin in the pituitary and hypothalamus and of GALR2/3 in the pituitary decreased, and the GnRH, LHβ, and FSHβ expression levels increased significantly. This suggests that a long photoperiod regulates reproductive activities by activating the gonadotrope-axis, which is modulated by decreased spexin levels.